Antioxidant, Anti-Proliferative And Bronchodilatory Activities Of Euphorbia Hirta Extracts - Chen, YS; Er, HM (Malaysian Journal of Science, 2010)
Euphorbia hirta is a plant commonly found in wild lands in tropical countries. It has various medicinal uses such as for conjunctivitis, ulcerated cornea, asthma, bronchitis, upper respiratory catarrh etc. In this study, crude n-hexane, chloroform, methanol and water extracts of the plant were screened for their antioxidant activities using an improved 2, 2’-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical cation decolorisation assay method. The methanol and water extracts showed comparable antioxidant activities to those of green and black teas. On the other hand, the chloroform and n-hexane extracts did not show significant antioxidant activities. The extracts were also screened for anti-proliferative acitivities against normal mouse fibroblast cells (NIH/3T3). Results indicated that the methanol and chloroform extracts were less anti-proliferative than the water and hexane extracts. The effect of Euphorbia hirta aqueous extract on guinea pig trachea was studied. The water extract alone did not have any effect on the guinea pig trachea but it showed partial inhibition on the histamine induced tracheal smooth muscles contractions. Therefore, further studies may focus on water extract as it showed considerable antioxidant activity and partial inhibitory effect on histamine induced tracheal smooth muscle contractions. (Keywords: Antioxidant activity; Bronchodilation; Anti-proliferative activity; Euphorbia hirta; Plant extracts.)